Comparison of the use of graft augmented tubularized split (GATS) and tubularized incised plate urethroplasty (TIPU) techniques for hypospadias repair in patients with narrow plate and small glans - Karagözlü Akgül, Ahsen; Abidoğu, Sadık; Kıyan, Gürsu; Adalı, Embiye; Tuğtepe, Halil (Journal of Surgery and Medicine, 2022)
Background/Aim: Hundreds of repair techniques were described for hypospadias repair. It is still a problem to choose the right technique in hypospadias repair for patients with narrow plate and small glans, because the patients with narrow urethral plate and small glans usually suffer from complications. GATS (Glans Augmented Tubularized Split) is an alternative technique with different details from grafted TIPU (Tubularized Incised Plate Urethroplasty). The aim of this study is to compare the outcomes of TIPU and GATS procedures on these difficult cases. Methods: This retrospective cohort study consists of the analysis of patients who underwent GATS and TIPU procedures in our department between January 2017 and January 2020. Patients with distal and midpenile hypospadias and with shallow groove, glans smaller than 17 mm, and plate narrower than 8mm were included the study. Patient with follow-up shorter than 1 year or incomplete data and secondary cases were excluded. Patients were divided into two groups according to the technique performed, as 25 patients in TIPU group and 20 patients in GATS group. Results: The mean diameter of glans were 15.3 mm and 14.5 mm, mean width of plate were 5.2 mm and 4.1 mm in TIPU and GATS groups respectively. Complications were observed in 7 (28%) patients of TIPU group and in 2 (10%) patients of GATS group (P>0.05). Urethral stenosis in one patient, urethral fistula in two patients, urethral dehiscence in two and urethral stenosis and diverticula in one patient, urethral stenosis and fistula in one patient were detected in TIPU group. Urethral fistula in one patient and urethral dehiscence in one patient were observed in GATS group. Conclusion: GATS procedure is an alternative method for difficult cases with narrow urethral plate and small glans with less complications than TIPU technique.